2010
DOI: 10.1016/j.str.2009.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Zernike Phase Plate Cryoelectron Microscopy Facilitates Single Particle Analysis of Unstained Asymmetric Protein Complexes

Abstract: Single particle reconstruction from cryoelectron microscopy images, though emerging as a powerful means in structural biology, is faced with challenges as applied to asymmetric proteins smaller than megadaltons due to low contrast. Zernike phase plate can improve the contrast by restoring the microscope contrast transfer function. Here, by exploiting simulated Zernike and conventional defocused cryoelectron microscope images with noise characteristics comparable to those of experimental data, we quantified the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 66 publications
2
26
3
Order By: Relevance
“…This study showed that the number of images was reduced by ~30% to get the same resolution, compared to a reconstruction from conventional images. Such data reduction is smaller than the theoretical expectation (Chang et al, 2010). In our current study, we combined a state-of-the-art electron cryomicroscope equipped with a C-film phase plate at the focal plane of the objective lens for data collection and data processing method for image reconstruction.…”
Section: Introductioncontrasting
confidence: 56%
“…This study showed that the number of images was reduced by ~30% to get the same resolution, compared to a reconstruction from conventional images. Such data reduction is smaller than the theoretical expectation (Chang et al, 2010). In our current study, we combined a state-of-the-art electron cryomicroscope equipped with a C-film phase plate at the focal plane of the objective lens for data collection and data processing method for image reconstruction.…”
Section: Introductioncontrasting
confidence: 56%
“…The amount of phase contrast that is shown in our simulations is significantly greater than that reported by Chang et al (Chang et al, 2010), who also modelled Zernike phasecontrast image formation for macromolecules embedded in vitreous ice. We believe that the discrepancy in results is due mainly to the fact that Chang et al did not apply a sufficiently low cut-on frequency to produce the full effect that can be achieved with a phase plate.…”
Section: Discussioncontrasting
confidence: 76%
“…The simulated imaging system can be used to generate raw image datasets, which in the current work were for a fixed electron energy of 200 keV, that can then be processed in the same way that is used for experimental data, giving insight into the practical advantages of phase contrast microscopy. While Chang et al have recently investigated this question in detail (Chang et al, 2010), we show here that their investigation underestimates the improvement in contrast and signal-to-noise ratio that is achievable at low spatial frequencies, due to using a rather high value for the cut-on frequencies in their simulations…”
Section: Introductioncontrasting
confidence: 62%
“…And, complexes smaller than 200 kDa remain challenging because of low signal-to-noise ratios in the images. Therefore, continuing developments of sample preparation (Russo and Passmore, 2014a, b) and image processing techniques, as well as the development of even better detectors and the commercialization of phase plates, which will allow imaging smaller particles (see (Chang et al, 2010; Danev et al, 2014) for two recent, commercialized implementations), may likely lead to even further improvements in the near future.…”
Section: Discussionmentioning
confidence: 99%